2004
DOI: 10.1897/02-635
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral response of young rainbow trout (Oncorhynchus mykiss) to forest fire‐retardant chemicals in the laboratory

Abstract: Fire-retardant chemicals often are applied in relatively pristine and environmentally sensitive areas that are potentially inhabited by endangered or threatened aquatic species. Avoidance of contaminants is an adaptive behavior that may reduce exposure to harmful conditions. We evaluated the avoidance responses of rainbow trout (Oncorhynchus mykiss) to concentrations of fire-retardant chemicals and alternate constituent formulations ranging from 0.65 to 26 mg/L. Countercurrent avoidance chambers were used in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
2
10
0
4
Order By: Relevance
“…The avoidance sensitivity of D. rerio to copper in the present study (24‐h EC50 of 16 μg/L) was consistent with that reported by Steele et al [4] (a copper threshold eliciting avoidance of 10 μg/L) and to that (differed by a factor of two) reported for Pimephales promelas Rafinesque [31], Salmo trutta Linnaeus, and Oncorhynchus mykiss (Walbaum) [3]. The observed avoidance response to copper was also found to be lower than previously reported 96‐ and 24‐h LC50 values, by a factor of approximately 3 to 9 [24,32,33] and 12 to 22 [33], respectively, corroborating other studies showing that avoidance is a response more sensitive than lethality for fish [6,8] as well as for cladocerans [7], amphipods [5], and oligochaeta [2]. A composite sample representative of the avoidance EDil50 (2% AMD) was analyzed (by inductively coupled plasma spectrophotometry [34]) for total metals revealing the following concentrations of the metals known to be among the most concentrated in the AMD [26,27]: 146 μg/L Cu, 322 μg/L Zn, and 605 μg/L Mn.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The avoidance sensitivity of D. rerio to copper in the present study (24‐h EC50 of 16 μg/L) was consistent with that reported by Steele et al [4] (a copper threshold eliciting avoidance of 10 μg/L) and to that (differed by a factor of two) reported for Pimephales promelas Rafinesque [31], Salmo trutta Linnaeus, and Oncorhynchus mykiss (Walbaum) [3]. The observed avoidance response to copper was also found to be lower than previously reported 96‐ and 24‐h LC50 values, by a factor of approximately 3 to 9 [24,32,33] and 12 to 22 [33], respectively, corroborating other studies showing that avoidance is a response more sensitive than lethality for fish [6,8] as well as for cladocerans [7], amphipods [5], and oligochaeta [2]. A composite sample representative of the avoidance EDil50 (2% AMD) was analyzed (by inductively coupled plasma spectrophotometry [34]) for total metals revealing the following concentrations of the metals known to be among the most concentrated in the AMD [26,27]: 146 μg/L Cu, 322 μg/L Zn, and 605 μg/L Mn.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, avoidance behavior can be a sensitive indicator of contaminant effects. Avoidance has been shown to be more sensitive than lethality or other sublethal responses, in some cases responding to levels lower than the maximum permissible values for contaminants in the environment [1,2,4–8]. Therefore, avoidance should be considered as a complementary sublethal response to improve ecological relevance in the assessment of the environmental risks of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, avoidance behavior can be a sensitive indicator of contaminant effects. Avoidance has been shown to be more sensitive than lethality or other sublethal responses, in some cases responding to levels lower than the maximum permissible values for contaminants in the environment [1,2,[4][5][6][7][8]. Therefore, avoidance should be considered as a complementary sublethal response to improve ecological relevance in the assessment of the environmental risks of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Most avoidance systems expose the organisms to a nonlinear toxicant gradient in systems often simply consisting of a two-option design [3][4][5][6]13]. Moreover, the avoidance response is generally expressed as an estimate of a lowest-observed-effect concentration [2,3,[8][9][10]. Yet avoidance should ideally be quantified in the form of a point estimate of the effective concentration toward a certain percentage of test organisms (e.g., the median avoidance effective concentration [EC50]) to allow sensitivity comparisons between avoidance tests as well as between avoidance and other endpoints [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated avoidance of contaminants by aquatic organisms, namely cladocerans (Lopes et al 2004), amphipods (Kravitz et al 1999;De Lange et al 2006), chironomid larvae (Wentsel et al 1977), and fish (Å tland and Barlaup 1995;Svecevičius 2001;Wells et al 2004;Moreira-Santos et al 2008). Although avoidance responses may have important ecological implications, even at the ecosystem level (Little et al 1993;Lopes et al 2004), and occur at levels of contamination below those causing lethal and sublethal effects (Little et al 1993;Wells et al 2004;Lopes et al 2004), avoidance-based aquatic tests have not been included in risk assessment studies. Furthermore, almost all ecotoxicological tests that have been proposed involve the exposure of the test organisms in a confined system, i.e., their forced exposure to the toxicants.…”
mentioning
confidence: 99%